Synthesis, Characterization and Anticancer Activity of (5,1-Substituted)-3-(indoline-4-(thiophene-2-yl-methylene)-2-(p-tolyl)-2-methylene)-4,3-dihydro-1H-imidazole-5-one Derivatives - Bayya, Chandraprakash; Manda, Sarangapani (Asian Journal of Chemistry, 2021)
The synthesis of novel imidazole-5-one derivatives (5a-j) was allowed in a conventional method by way of Erlenmeyer and Schiff base mechanism. Compound 2a was synthesized by Erlenmeyer reaction of N-(4-methoxy benzoyl)glycine with 2-thiophene-carboxaldehyde in the presence of acetic anhydride and anhydrous sodium acetate. Finally, it undergoes dehydration reaction with Schiff bases of isatin derivatives (4a-j) to yield final compounds 5a-j. The organic potentials of the newly synthesized imidazole-5-one derivatives have been evaluated for their in vitro anticancer activity by MTT assay method. It against MCF-7 cells as comparison with doxorubicin popular drug. The synthesized compounds 5e, 5f and 5j exhibited excellent anticancer activity against MCF-7 cell lines.